IMPLEMENTASI KURIKULUM SEKOLAH ALAM DALAM PEMBENTUKAN PENDIDIKAN KARAKTER PESERTA DIDIK DI SEKOLAH ALAM AL KARIM LAMPUNG - Marilin Kristina; Ruly Nadian Sari; Dwi Puastuti (Universitas Islam Negeri Alauddin Makassar, 2021)
Abstract: Implementation of The Natural School Curriculum in The Formation of Character Education for Students at The Al Karim Natural School in LampungThe purpose of this study was to describe the implementation of the natural school curriculum in the formation of student character education at the Al Karim Alam School, Lampung. This research is included in field research and the type of research used is qualitative research. The presentation of the data in this study uses descriptive data presentation with the method of interview, observation and documentation. The results obtained in this study are that the Al Karim Lampung natural school has four additional curriculum models besides the K13 curriculum, namely the Islamic Morals Curriculum, Science Logic Curriculum, Leadership Curriculum, and Entrepreneurship Curriculum. These four curricula are then revealed into various learning methods that can shape the character of students, especially religious and independent characters as outlined through the learning process carried out. Abstrak: Implementasi Kurikulum Sekolah Alam dalam Pembentukan Pendidikan Karakter Peserta Didik di Sekolah Alam Al Karim LampungTujuan dari penelitian ini adalah mendeskripsikan implementasi kurikulum sekolah alam dalam pembentukan pendidikan karakter siswa di Sekolah Alam Al Karim Lampung. Penelitian ini termasuk dalam penelitian lapangan atau field research dan jenis penelitian yang digunakan adalah penelitian kualitatif. Adapun penyajian data dalam penelitian ini menggunakan penyajian data deskriptif dengan metode wawancara, observasi dan dokumentasi. Hasil perolehan dalam penelitian ini adalah Sekolah Alam Al Karim Lampung memiliki empat model kurikulum tambahan selain kurikulum K13 yaitu Kurikulum Akhlak Islamika, Kurikulum Logika Sains, Kurikulum Leadership, dan Kurikulum Entrepreneurship. Keempat kurikulum ini kemudian diturunkan ke dalam berbagai metode pembelajaran yang dapat membentuk karakter peserta didik khususnya karakter religius dan mandiri yang dituangkan melalui proses pembelajaran yang dilakukan.